Determining the Isometric Point of the Knee - Stannard, James P.; Hammond, Allan; Tunmire, Danny; Clayton, Matthew; Johnson, Chris; Moura, Cid (The Journal of Knee Surgery, 2012)
Posteromedial and posterolateral reconstructions of the knee are frequently required in the management of knee dislocations. This study compares the accuracy of radiographic reference points to established anatomical landmarks in reproducing the isometric points of the posteromedial corner and posterolateral corner (PLC) of the knee. Posteromedial and posterolateral surgical approaches were made in 20 cadaveric knees. The posteromedial and posterolateral isometric points of each femur were determined using the anatomic landmarks and radiographic reference points in a randomized order. An Isometer was used to measure the displacement, to the nearest millimeter; knees were passed into flexion. A two-tailed t-test was used to analyze the data and statistical significance was set to p < 0.05. For the isometric point of the PLC, the radiographic method resulted in a mean displacement of 1.63 mm as the knee was passed from extension into flexion, while the anatomic method had a mean displacement of 4.84 mm (p < 0.00018). The mean displacement on the posteromedial side using the radiographic method was 2.10 mm as the knee was passed from extension into flexion, while the anatomic method resulted in 3.21 mm of displacement (p = 0.074).
Keywords: isometric point; posteromedial ligament reconstructions; posterolateral ligament reconstructions; radiographic reference points